Pengembangan dan Pemanfaatan Tema Pembelajaran Dalam Penggubahan dan Penciptaan Lagu Anak Usia Dini - Itot Bian Raharjo (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2021)
Learning in early childhood education cannot be separated from musical activities. In practice, musical activities can be carried out to develop 5 aspects of early childhood development, including aspects of cognitive development, religious and moral values, language, physical motoric, and social emotional. This study uses a qualitative descriptive approach with the research subjects being IGTKI and IGRA teachers in Kediri Regency who are taking PG-PAUD lectures at Nusantara University PGRI Kediri with a study period in semester V with a total of 20 respondents. It can be identified that they have various musical abilities, namely solfegio skills, the ability to play melodic instruments, and can't play music. Data obtained through interviews, documentation, and observation. Data analysis using interactive analysis. It can be concluded that composing song lyrics can increase creativity and creating new songs is an alternative choice in increasing the vocabulary of early childhood songs.